Compassion in practice—Evaluating the awareness, involvement and perceived impact of a national nursing and midwifery strategy amongst healthcare professionals in NHS Trusts in England. Issue 5 (27th February 2018) - O'Driscoll, Mike; Allan, Helen; Liu, Liang; Corbett, Kevin; Serrant, Laura
Abstract : Aims and objectives: To report the findings from an evaluation of the impact of the Compassion in Practice Vision and Strategy (National Health Service England (NHSE), 2012) on nursing, midwifery and care staff. Background: The Compassion in Practice Vision and Strategy was a programme of work to highlight the importance of compassionate care following the Francis Report in 2013 into the deficits in care in an NHS Hospital Trust. It was launched by NHS England in 2012 at a time when fiscal cuts were introduced by the Department of Health in England. Design and setting: Mixed methods. Results: Inferential statistics were used to test whether there were significant differences between staff at different levels of seniority with regard to awareness and involvement in Compassion in Practice Vision and Strategy and their attitudes to it. Awareness and involvement of staff in Compassion in Practice Vision and Strategy were high amongst middle and senior management but limited at ward level. Staff involvement in Compassion in Practice Vision and Strategy was limited due to a lack of awareness. Ward level staff who were aware and involved, perceived a lack of support and communication from senior leadership to deliver the Compassion in Practice Vision and Strategy. Discussion: Results reveal professional anger, distress and resistance to the Compassion in Practice Vision and Strategy and a view of the programme as a top‐down initiative which did not sufficiently recognise structural constraints on nurses' ability to deliver compassionate care. We discuss the implications of our findings for global nursing. Conclusion: Participants emphasised that compassion for patients is only sustainable where there is compassion for staff and many participants felt that they were not being treated with compassion. Relevance for clinical practice: National Health Service England should strongly affirm that nurses and midwives in general provide compassionate care. Trust leadership should provide support for ward level staff who deliver compassionate care in difficult circumstances.